SPIRITUALITY AND RELIGIOUSITY IN A CONTEXT OF PSYCHOSOCIAL CARDIOVASCULAR RISK FACTORS - E. О. Taratukhin (Кардиоваскулярная терапия и профилактика, 2017)
Aim.  To investigate  on  psychological  parameters of  spiritiality  and religiousness as events taking place during psychosocial rehabilitation of post myocardial infarction (MI) patients.Material  and  methods. Into the  study,  103  patients  (45  females) included, after an event of MI (≥3 days, during admittance).  Mean age Me  (Q1;Q3)  =64,0  (56,0;77,5)   y.o.,  females  were  older  — 71,5 (66,5;80,3)  y., males  — 60,0(53,0;66,0)  y. Comparison group  (n=30) consisted  of equal  by demographics but  with no significant somatic pathology paersons. The questionnaire was applied, of daily experienced spirituality, with ranging of experiences  from “never” to “permanently” (from 1 to 6, respectively). Also, a semi-structured interview was done with further descriptive phenomenological analysis.Results. It is found, that the level of daily spiritual experience is at the level of “rarely or never”, and a request  to spiritual menanings itself is related  mostly to the situation of disease  than exists as a separate experience.  The summ of points by the score was M±σ =34,32±7,08 of maximum 84; females had 36,02±8,44,  males 33,05±5,61 (р=0,034). Comparison group had significantly higher score, but with low difference — 39,23±7,14 (р=0,001). In comparison, females also had  higher  score  — 41,73±7,69  and  36,73±5,74  (in comparison р=0,053; in relation to the patients р=0,024 for females and р=0,027 for males).Conclusion. Quite a low level of the experienced spirituality, revealed in patients  after MI can be interpreted  as a potential cardiovascular risk factor, and at least is a point for further research.